Yupik language instruction in Gambell (Saint Lawrence Island, Alaska) - Koonooka, Christopher (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2005)
AbstractThe first part of the paper is about the current status of Yupik language instruction in Gambell, Saint Lawrence Island (Alaska). Problems began after key supporters and teachers left the successful Yupik language program in Gambell schools which had been running for at least 25 years. Federal and state changes to education made it more difficult to run the program, but the school district and school still keep the Yupik staff to bring back their Yupik program as it used to be. The second part of the paper is a personal description of a recent language and publication project to translate into English and transcribe into Yupik old Siberian Yupik folk-stories originally recorded and published in Russian cyrillic-based Yupik orthography, so they could be used in the classroom. Political and social boundaries had prevented for 40 years Yupik families from America and Russia to interact, but this university funded project allowed new contacts, and investigations with elders on words included in the book revealed their lost meanings.